PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA FBM WORLDWIDE - Munir Azhari (Sekolah Tinggi Manajemen IMMI Jakarta, 2021)
The effect of service quality on customer satisfaction in FBM WORLDWIDE. The study aims to determine service quality to customer satisfaction correlation and influence score at FBM WORLDWIDE. The method used is a survey method by using questionnaires to respondents as many as 75 respondents from customers/users of FBM WORLDWIDE delivery services. The data used are descriptive analysis, simple linear regression analysis, R test, T-test, and hypothesis testing. The results show that the service quality variable simultaneously had a positive and significant effect on customer satisfaction. The type of research is the quantitative method. Furthermore, Data collection techniques use carried out through survey methods. The number of samples is 75 people. The results of this study use statistical data methods with the SPSS (Statistical Package For Social Science) version 21 program. The results of the analysis state that the relationship between variable X (service quality) and variable Y (customer satisfaction) is forceful. It can be seen from the R-value of 0.903 so that it is close to 1. The influence of service quality variable (X) to customer satisfaction variable (Y) score is 0.813 or 81,3%. Furthermore, the rest is influenced by other factors. The T-count value is 17.980 and T-table is 1.993 (based on the table), so T-count is greater than T-table which means Ha is accepted and Ho is rejected, meaning that the X variable (quality of service) is very related and has a significant effect on the Y variable (customer satisfaction).